THE MEDIATING EFFECT OF INNOVATION PERFORMANCE ON EXTERNAL SUSTAINABLE MANUFACTURING PRACTICE AND SOCIAL SUSTAINABILITY LINKAGE (Journal of Technology and Operations Management, 2017)
This paper analyzes the mediating effect of four dimensions of innovation performance (IP) namely product innovation, process innovation, organizational innovation, and marketing innovation on the relationship between external sustainable manufacturing practice (external SMP) and social sustainability. Employing partial least squares-structural equation modeling (PLS-SEM) approach, the survey data collected via mailed questionnaire were analyzed. In total, 150 responses were obtained from manufacturing firms in Malaysia with a diverse range of industries. Out of four dimensions of IP, the empirical results indicate that organizational innovation performance is the single significant mediator on the causal linkage between external SMP and social sustainability. While providing a clearer picture of the interrelationship among external SMP, IP, and social sustainability, the results of this study could help owners and managers in assessing their firm performance particularly related to social sustainability and innovation performance as well as identify the strength and weaknesses of their current practices. In addition, the findings of this study could provide an important source of information for government and other policy makers in promoting social sustainability awareness and external SMP implementation particularly among firms in manufacturing industries.